ANALISIS PEMBINAAN DAN PENGEMBANGAN OLAHRAGA DAYUNG ROWING DI JAWA BARAT BERDASARKAN SPLISS MODEL - Anang Mulyana, - (2022)
Analysis of The Coaching and Development of Rowing Sport in West Java Based On Spliss Model Anang Mulyana, Amung Ma'mun, Dede Rohmat Nurjaya Universitas Pendidikan Indonesia, Bandung, Jawa Barat, Indonesia anangmulyana@upi.edu ABSTRACT This study aims to determine the program for coaching and developing the achievement of rowing Sports in the rowing of West Java Province by using the "Sports Policy Factors Leading to International Sporting Success" (SPLISS) Model Approach. The method used in this research is descriptive qualitative method. Data collection techniques using the method of observation, interviews, and documentation. The data analysis technique in this study is in the field of the Miles and Huberman model. The sampling technique used was purposive sampling. The number of samples was 6 people, namely administrators, coaches and rowing athletes in West Java rowing numbers. The results of the study are as follows; 1) Budget management can be said to be good, this is indicated by the delivery of financial processes by direct transfer to the person concerned and also the presence of sponsors from other parties other than KONI, namely the chairman of Pengda rowing West Java, 2) Policy development in terms of coaching and the development of rowing achievement in West Java as a whole is in accordance with the duties of the Parent Organization of Sports Branches, although there are still things that must be improved and improved 3) Community participation in playing rowing has increased which, 4) Identification and development are in accordance with Law Number 11of 2022, 5) West Java PODSI has not fully provided support to athletes who are no longer actively defending the name of West Java, however as long as they are athletes they get career support. 6) Equipment support from the Regional Government through KONI has increased along with the increase in rowing Sports achievements, 7) West Java PODSI currently has many qualified trainers. and experience in handling a team, 8) PODSI Jawa Ba rat has organized a competition, but the competition has not been held in stages and continuously, 9) West Java PODSI has developed training, Sports science and Sports medicine, although it still needs to be improved. Keywords: Analysis, Achievement Coaching and Development Program Rowing